The add-on effect of Shufeng Jiedu capsule for treating COVID-19: A systematic review and meta-analysis - Sheng, Xiaodi; Chen, Chao; Jiang, Guowang; Ji, Zhaochen; Guo, Zehui; Hu, Haiyin; Wang, Hui; Zhai, Jingbo; Zhang, Dong; Zhang, Junhua; Guo, Liping (Frontiers in Medicine, 2022)
Introduction: Shufeng Jiedu capsule (SFJD) is a commonly used Chinese patent medicine in China, and has been recommended for people during the medical observation period of COVID-19. Furthermore, some studies have reported that SFJD has therapeutic effects in patients diagnosed with COVID-19. Therefore, the present systematic review aims to critically evaluate the efficacy and safety of SFJD combined with western medicine (WM) for treating COVID-19. Methods: A literature search concerning WHO COVID-19 database, PubMed, Embase, Cochrane Library, the Web of Science, CKNI, Wanfang, VIP, CBM and clinical trial registries was conducted, up to August 1, 2022. Randomized controlled trials (RCTs), non-RCTs, cohort studies and case series of SFJD combined with WM for COVID-19 were included. Literature screening, data extraction, and quality assessment were performed independently by two reviewers in line with the same criteria. We used the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) to assess the certainty of evidence. Meta-analyses were performed with Revman 5.3 if possible. The descriptive analysis was conducted when the studies could not be meta-analyzed. Results: Totally 10 studies with 1083 patients were included. Their methodological qualities were moderate. The certainty of evidence was mainly low due to the observational study design. The results demonstrated that compared to WM group, SFJD + WM group remarkably increased the nucleic acid negative conversion rate (RR=1.40, 95%CI: 1.07 to 1.84), total effective rate (RR=1.18, 95%CI: 1.07 to 1.31), cure rate (RR=4.06, 95%CI: 2.19 to 7.53), and the CT improvement rate (RR=1.19, 95%CI: 1.08 to 1.31), shorten nucleic acid negative conversion time (MD= -0.70, 95%CI: -1.14 to -0.26), reduced the clinical symptom disappearance time (fever, diarrhea, cough, fatigue, pharyngalgia, nasal congestion, and rhinorrhea), as well as improved the levels of laboratory outcomes (CRP, IL-6, Lym and Neu). Additionally, the incidence of adverse reactions did not exhibit any statistically significant difference between SFJD + WM group and WM group. Conclusion: SFJD combined with WM may be more effective than WM alone for the treatment of COVID-19. However, more well-designed RCTs still are warranted.